Facilitated detection of social cues conveyed by familiar faces - Visconti di Oleggio Castello, Matteo; Guntupalli, J. Swaroop; Yang, Hua; Gobbini, M. Ida (Frontiers in Human Neuroscience, 2014)
Recognition of the identity of familiar faces in conditions with poor visibility or over large changes in head angle, lighting and partial occlusion is far more accurate than recognition of unfamiliar faces in similar conditions. Here we used a visual search paradigm to test if one class of social cues transmitted by faces – direction of another’s attention as conveyed by gaze direction and head orientation – is perceived more rapidly in personally familiar faces than in unfamiliar faces. We found a strong effect of familiarity on the detection of these social cues, suggesting that the times to process these signals in familiar faces are markedly faster than the corresponding processing times for unfamiliar faces. In the light of these new data, hypotheses on the organization of the visual system for processing faces are formulated and discussed.